O efeito dos fatores locais e de preditores espaciais sobre a estrutura das algas perifíticas em planície de inundação : uma perspectiva de metacomunidade. - Algarte, Vanessa Majewski (2014)
One of the major objectives of community ecology is to comprehend the pattern of species distribution as well as which factors make them abundant. Studies verifying such patterns of community distribution seek to comprehend how local conditions and dispersion effects establish a community structure. This perspective enables a broader view of patterns of species distribution and the processes leading changes in community structures. In this context, the key objective of this study was to assess the spatial variation for the structure of periphytic algal community in 30 floodplain environments in upper Paraná River during March 2010. The relationship between species of periphytic algae and environmental, spatial variables was also assessed. Therefore, this study was divided into two chapters. The first chapter "Unraveling the variation in richness of periphytic algae community according to a deconstructive approach" aimed especially at assessing the relative importance of local and spatial factors on the richness of communities species as a whole subsequently being decomposed in taxonomic classes and adherence strategies, e.g., firmly and loosely. The second chapter "Partitioning of the variation in deconstructed periphytic algal communities: does the use of biological traits matter?? aimed at assessing the variation in the composition of algal groups species with distinct dispersion abilities based on species biological traits concerning both environmental and spatial variables. In general, the results obtained through the assessment of periphytic algae community variation in upper Paraná River floodplain revealed that environmental factors proved predominant in establishing the community structure. Nevertheless, some of the algal groups presented a strong spatial component regarding dispersion limitation. Furthermore, the deconstruction of the periphytic algal community for groups based on taxonomy and biological traits enabled a better understanding of the processes involved in establishing the variation pattern for this community.